2001
DOI: 10.1074/jbc.m104105200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein Differentially Activates RAS-RAF-MAPK and JNK Pathways in X-transforming Versus Non-transforming AML12 Hepatocytes

Abstract: The hepatitis B virus (HBV) X protein (pX) is impli-Patients chronically infected with hepatitis B virus develop hepatocellular carcinoma (HCC) 1 in their 4th or 5th decade (1). The 16.5-kDa X protein, encoded by HBV, is implicated in HCC pathogenesis (2). Despite numerous studies describing pX activities, the molecular mechanism by which pX affects hepatocyte transformation is unknown. This study addresses aspects of the pX-mediated mechanism of hepatocyte transformation.It is well accepted that pX is a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 71 publications
(80 reference statements)
4
91
0
Order By: Relevance
“…In addition, pX sensitizes hepatocytes to apoptosis in response to weak apoptotic stimuli, such as subapoptotic concentrations of transforming growth factor ␤ (TGF-␤) or TNF-␣ (43,69) by an unknown mechanism. pX induces the activation of mitogenic Ras-Raf-MAP kinase (5,23,73), JNK (6,73), and p38 MAP kinase (72) pathways via calcium-regulated activation of c-Src (9,44). Importantly, earlier studies (72,73) employing pXexpressing hepatocyte cell lines demonstrated that tetracycline-regulated pX differentially activates the Ras-Raf-MAP kinase, JNK, and p38 MAP kinase pathways in differentiated versus less differentiated hepatocytes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, pX sensitizes hepatocytes to apoptosis in response to weak apoptotic stimuli, such as subapoptotic concentrations of transforming growth factor ␤ (TGF-␤) or TNF-␣ (43,69) by an unknown mechanism. pX induces the activation of mitogenic Ras-Raf-MAP kinase (5,23,73), JNK (6,73), and p38 MAP kinase (72) pathways via calcium-regulated activation of c-Src (9,44). Importantly, earlier studies (72,73) employing pXexpressing hepatocyte cell lines demonstrated that tetracycline-regulated pX differentially activates the Ras-Raf-MAP kinase, JNK, and p38 MAP kinase pathways in differentiated versus less differentiated hepatocytes.…”
mentioning
confidence: 99%
“…pX induces the activation of mitogenic Ras-Raf-MAP kinase (5,23,73), JNK (6,73), and p38 MAP kinase (72) pathways via calcium-regulated activation of c-Src (9,44). Importantly, earlier studies (72,73) employing pXexpressing hepatocyte cell lines demonstrated that tetracycline-regulated pX differentially activates the Ras-Raf-MAP kinase, JNK, and p38 MAP kinase pathways in differentiated versus less differentiated hepatocytes. In differentiated hepatocytes, modeled by the AML12 3pX-1 cell line, conditional pX expression activates the Ras-Raf-MAP kinase pathway in a sustained manner (72).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These factors are involved in junB gene expression via MAP kinase pathways like p38, and ERK or via the JAK/STAT pathway (22,27,28,(36)(37)(38)(39)(40)(41)(42)(43)(44). A previous report verified that p38 was activated by various stress conditions, such as osmotic stimulus or cytokine, suggesting its relationship to cell death (45)(46)(47)(48)(49). ERK induced cell growth and differentiation and regulated cell cycle transition (50)(51)(52).…”
Section: Discussionmentioning
confidence: 95%
“…9 Other studies have shown that the HBX protein of HBV augments Ras/Raf/MAPK signal transduction, which contributes to cell proliferation and survival. 34 From this evidence, we expected that Chang-HBX cells should harbor more active Ras protein when compared with Chang-vec cells. When we compared Ras expression in cell lysates from the two cell lines, we found that Ras protein is increased somewhat in abundance in Chang-HBX cells compared with that of Chang-vec cells (Figure 3a).…”
Section: Hbx Expression Causes Resistance To Reovirus-induced Apoptotmentioning
confidence: 99%